Pengaruh Kepemimpinan Transaksional dan Motivasi Ekstrinsik Terhadap Kinerja Pegawai Dengan Variabel Intervening Kepuasan Kerja - Adissya Maya Andara (GEMILANG: Jurnal Manajemen dan Strategi Bisnis, 2020)
The role of the leader is a strategic factor that drives the performance of the organization's members. This study aims to examine the effect of transactional leadership and extrinsic motivation on employee performance with job satisfaction as intervening. The study was conducted at PT Anindita Niaga Galantri - Honda Auto Serang by distributing questionnaires to 50 sales & marketing divisions. Data analysis using Structural Equation Model of Partial Least Square (SEM PLS). The results showed that extrinsic motivation had significant effect on job satisfaction and transactional leadership had a significant effect on employee performance. While transactional leadership has no effect on job satisfaction; extrinsic motivation has no effect on job satisfaction and job satisfaction has no effect on employee performance. Low levels of salary and high job pressures make job satisfaction can not be an intervening effect on employee performance at PT Anindita Niaga Galantri - Honda Auto Serang.